A second look at efficacy criteria for onychomycosis: clinical and mycological cure - Ghannoum, M.; Isham, N.; Catalano, V. (British journal of dermatology (1951), 2014)
Summary Background Approval of topical onychomycosis drugs by regulatory agencies may be negatively impacted by an overly stringent definition of complete cure, which includes nail clearing plus mycological cure. Objectives In this position paper, we discuss interpretation of mycological outcome and clinical trial length. Methods We reviewed data from seven international onychomycosis trials that enrolled subjects with positive KOH and dermatophyte‐positive culture at screening followed by 48 weeks of treatment. Further, we examined 94 KOH‐positive/culture‐negative week 52 follow‐up samples for morphological hyphal damage. Results From 3054 samples collected at week 52 follow‐up visits, 2360 were culture‐negative. However, a significant percentage (78·7%) of these subungual samples (n = 1857) remained KOH‐positive. From the subset of follow‐up samples examined for morphological changes, we identified hyphal breakage or distortion in 56 direct smears (60%), which may indicate nonviability. Conclusions Reassessment of the definition of onychomycosis cure is critical. For clinical trials of topical agents, length of treatment should be re‐examined. Further, in our experience, a high rate of subungual debris samples remained direct smear‐positive while converting to negative culture. Evidence of morphological hyphal damage suggests that late‐visit microscopic results may be false‐positives. Therefore, the absence of clinical signs following an adequate washout period, coupled with a negative culture, with or without negative microscopy, should be considered the definition of onychomycosis cure. What's already known about this topic? Onychomycosis mycological cure is currently defined as a negative KOH and negative dermatophyte culture. What does this study add? The current definition of onychomycosis complete cure is too stringent. Microscopy of late‐visit samples may demonstrate nonviable hyphae. Onychomycosis cure should be defined as the absence of clinical signs or presence of negative culture, with or without negative microscopy, assessed after an adequate washout period.